Persepsi Anak Jalanan Terhadap Kebutuhan Belajar Dan Bermain (Hak Anak) Di Sekoloh Kolong Langit Gunung Brintik Kota Semarang - Khotimah, Nur; ana, Di; Setiawan, Deni (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine how street children perceive the need to play and learn at the Kolong Langit Gunung Brintik School in Semarang city. The method used in this research is descriptive qualitative. The research subjects were three street children aged 4-7 years and two assistants from Kolong Langit Gunung Brintik School, Semarang City as informants. Sources of research data were collected through observation, interviews, and documentation. The validity of this research data is by triangulation. Data analysis in this study is data collection, data reduction, data presentation and verification or conclusion drawing. The results of this study indicate that the three street children who carry out activities on the streets are motivated by economic factors of parents, factors of low parental education, cultural factors of society. School under the sky as an alternative to provide assistance to children to fulfill children's rights, in this study the fulfillment of children's rights has not been fulfilled.